ESTABLISHMENT OF SLAG GRANULATION FOR CUPOLAS OF SMALL AND MEDIUM CAPACITY - N. N. Bardjugov; V. A. Zharanov; G. V. Gerasimova (Литьë и металлургия)
Compact mobile outfit and technology of waterstream granulation which can be successfully adapted to any production conditions of operating melting zones and departments are developed.